2016
DOI: 10.1111/nhs.12261
|View full text |Cite
|
Sign up to set email alerts
|

New Brunswick nurses' views on nursing research, and factors influencing their research activities in clinical practice

Abstract: New Brunswick became the first province in Canada to require a baccalaureate degree in nursing as the entry to practice, yet nursing research in hospital settings remains quite low. This study examined clinical nurses' views on nursing research, and identified some contributing factors to the research-practice gap. This descriptive, cross-sectional multicenter study involved 1081 nurses working in the Francophone Regional Health Authority in New Brunswick, Canada. Nurses were eager to identify nursing-care pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 32 publications
2
13
0
Order By: Relevance
“…Young nurses tended to partner with senior and research‐capable nurses to improve their own research skills. The collaboration between academic and clinical institutions was found to be an efficient way to promote nursing research capacity through sharing research infrastructure, clinical expertise and patient care responsibilities (Robichaud‐Ekstrand, ). It is believed collaborative efforts may help to promote a research culture in the hospital setting, facilitate the implementation of research projects (particularly data collection) and help nurses to engage in research activity (Scala, Price, & Day, ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Young nurses tended to partner with senior and research‐capable nurses to improve their own research skills. The collaboration between academic and clinical institutions was found to be an efficient way to promote nursing research capacity through sharing research infrastructure, clinical expertise and patient care responsibilities (Robichaud‐Ekstrand, ). It is believed collaborative efforts may help to promote a research culture in the hospital setting, facilitate the implementation of research projects (particularly data collection) and help nurses to engage in research activity (Scala, Price, & Day, ).…”
Section: Resultsmentioning
confidence: 99%
“…Nurses with a master's degree and above tended to value research more and had a favourable perception of their role in research when compared with nurses who had only obtained a diploma. They also had more research experience and involvement in research activity (Robichaud‐Ekstrand, ). Nurses who had worked more than ten years had richer research experience, when compared with those who had only worked for 1–5 years or less than one year (Robichaud‐Ekstrand, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is consistent with other studies that found a lack of mentors and other organisational resources were barriers to research activity (Roxburgh , Akerjordet et al . , Robichaud‐Ekstrand ). However, organisational resources alone are insufficient for the development of research activity.…”
Section: Discussionmentioning
confidence: 99%
“…, Evans et al . , Berthelsen & Holge‐Hazelton , Robichaud‐Ekstrand ) were the primary barriers to the conduct of research by nurses.…”
Section: Introductionmentioning
confidence: 99%